PERIKLANAN DALAM MEDIA BARU (Advertising In The New Media ) - Watie, Errika Dwi Setya (Jurnal The Messenger, 2012)
Advertising is currently getting a huge challenge. the number of ads , it is realized or not, effects on saturation of advertising. New era media presents new communications media to the community. This condition should be recognized by anyone working in the advertising, because the development of advertising is in line with a new media movement, so the expectansy of the intended market segment will be achieved better.Today, the challenge of a new style of advertising has been answered by the professions related to a new advertising which is driven by the appearance and the popularity of the new social media. One of the new profession known by and used in advertising is a Buzzer. The principle work of Buzzer is similar to WOM (Word Of Mouth). However, it should also be remembered that the selection of buzzer is also important, so that the purpose of advertising can be achieved.